55.6k views
2 votes
Use algebraic techniques to rewrite g(x)= (-7x^4+6x^8)/(x^3)

User Crytrus
by
6.0k points

1 Answer

3 votes

To solve this problem you must apply the proccedure shown below:

1. You have the following function given in the problem above:
g(x)= ((-7x^4+6x^8))/(x^3)

2. You can factor out the common term
x^(3) and simplify the function by using the properties of exponents, as following:


g(x)= (x^(3) (-7x+6x^5))/(x^3) \\ g(x)=-7x+6x^(5)

Therefore, the answer is:
g(x)=-7x+6x^(5)

User Namenlos
by
6.4k points